2023
DOI: 10.1007/s10802-023-01141-1
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders and Attachment Trauma in Adolescent Patients with Psychiatric Disorders

Manuela Gander,
Anna Buchheim,
Kathrin Sevecke

Abstract: This study examined how personality disorders (PD) differ with respect to gender, attachment status and traumatic childhood experiences in adolescent psychiatric inpatients. In particular, we investigated attachment-related traumatic material underlying adolescent PD. Our sample consisted of 175 inpatient adolescents aged 14 to 18 years (77% female, Mage = 15.13, SD = 1.35; 23% male, Mage =14.85, SD = 1.41). Thirty-nine patients (22%) fulfilled the diagnostic criteria for a PD according to the SCID-II PD: 51% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
(143 reference statements)
1
2
0
Order By: Relevance
“…The present study aimed to investigate the presence of personality subtypes in adolescent patients with DD according to the PDM-2 theoretical-clinical framework. Consistent with previous research (Feenstra et al , 2011 ; Gander et al , 2023 ), this investigation seems to confirm our first hypothesis, empirically supporting the great complexity in personality functioning of patients within this specific diagnostic grouping. Notably, in line with some investigations conducted on both adult and youth populations (Friborg et al ., 2014 ; Huprich et al , 2014 , Rost et al ., 2018 ; Westen et al , 2014 ), young depressed patients (compared with those with other clinical conditions) exhibited more maladaptive and clinically relevant traits of the emerging disorders of depressive, anxious-avoidant, narcissistic and borderline personality ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study aimed to investigate the presence of personality subtypes in adolescent patients with DD according to the PDM-2 theoretical-clinical framework. Consistent with previous research (Feenstra et al , 2011 ; Gander et al , 2023 ), this investigation seems to confirm our first hypothesis, empirically supporting the great complexity in personality functioning of patients within this specific diagnostic grouping. Notably, in line with some investigations conducted on both adult and youth populations (Friborg et al ., 2014 ; Huprich et al , 2014 , Rost et al ., 2018 ; Westen et al , 2014 ), young depressed patients (compared with those with other clinical conditions) exhibited more maladaptive and clinically relevant traits of the emerging disorders of depressive, anxious-avoidant, narcissistic and borderline personality ( Table 1 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the stability of personality pathology in young populations remains a contentious issue, the PDM grounds its diagnostic approach on the basis of a large body of scientific studies suggesting that specific maladaptive features of personality may be clearly identified in this developmental stage (Chanen, 2022 ; Lingiardi & McWilliams, 2017 ; Westen et al , 2014 ). Evidence has indicated that DD are strongly associated with personality disorders (mostly, clusters B and C) in adolescence (Feenstra et al ., 2011 ; Gander et al ., 2023 ; Ha et al ., 2014 ; Rost et al ., 2018 ; Westen et al ., 2014 ), and this comorbidity exerts a significant influence on prognosis and treatment outcomes (Strandholm et al ., 2014 ). Notably, young depressed patients often receive a diagnosis of borderline, dependent, avoidant, obsessive-compulsive, and depressive personality disorders (Feenstra et al ., 2011 ; Zanarini et al ., 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation